Post-disturbance carbon stocks and rates of sequestration: Implications on “blue carbon” estimates in Philippine mangroves - Salmo, Severino G, III (Archīum Ateneo, 2019)
Mangrove forest is one of the “blue carbon” ecosystems recognized for its high sequestration and long-term storage of carbon. While reports on blue carbon in mangroves are increasing, studies on the post-disturbance carbon stocks and rates of sequestration are still lacking in the Philippines. In this study, we assessed the stocks and rates of carbon sequestration in mangroves that were disturbed by typhoon and converted to aquaculture ponds. Carbon stocks were measured from the biomass and sediment compartments from typhoon-impacted sites (composed of natural and planted stands) and from mangrove-colonized abandoned fishponds. Using a stockchange approach, the rates of carbon sequestration were estimated at intra-annual and post-disturbance levels. Results showed wide variation in total carbon stocks and ranged from 168.96 to 355.70 Mg/ha (of which the biomass comprised 8.20 ± 4.18 % and the sediment with 92.84 ± 3.56 %). These values are 40-60 % lower than some SE Asian mangroves. Across sites, the post-disturbance rates of carbon sequestration (mean: 17.17 ± 0.57 Mg C/ha/yr) are similar with some studies and are within range from stands that are similarly recovering from disturbance. Our results indicate that disturbances contribute to changes in stocks and rates of carbon sequestration. Mangroves that colonized fishponds, although with relatively slower rates, have more stable carbon recovery. A more pro-active approach on the rehabilitation of abandoned fishponds (rather than leaving it to natural colonization process) is suggested to enhance carbon sequestration in Philippine mangroves.